Assessment of breast cancer treatment outcome at Tikur Anbessa Specialized Hospital Adult Oncology Unit, Addis Ababa, Ethiopia. Issue 2 (April 2019) - Dagne, Selamawit; Abate, Sefinew Migbaru; Tigeneh, Wondemagegnhu; Engidawork, Ephrem
Abstract: Introduction: Breast cancer is a leading cause of death worldwide, and ranks as the fifth cause of death from all cancers, and the most common cause of cancer death in women in both developing and developed countries. However, information regarding treatment outcome of breast cancer is scarce in Ethiopia. Objective: The aim of this study was therefore to assess treatment outcome among breast cancer patients at Tikur Anbessa Specialized Hospital. Method: Hospital-based retrospective cross-sectional study was conducted. Data were collected by reviewing the medical records and by phone interview. Result: A total of 303 patients were included in the study, more than one-fourth (31.02%) of the patients were in the age range of 30–39 years, with a mean age of 42.10 years. More than half (54.10%) of the patients were diagnosed to have breast cancer with clinical tumor, nodal status, and metastasis stage III breast cancer. The frequently used combination chemotherapy was FAC (5-fluorouracil, doxorubicin, and cyclophosphamide) in 66.9% patients. At the end of 3 years treatment follow-up, 46.53% of patients were dead, 34.32% were alive. Logistic regression analysis showed that age (adjusted odds ratio [AOR] = 0.32; 95% confidence interval (CI): 0.12, 0.95; P  = 0.040), chemotherapy cycle (AOR = 7.36; 95% CI: 2.28, 23.79; P  = 0.001), stage of the disease (AOR = 0.11; 95% CI: 0.05, 0.29; P  = 0.000), and endocrine therapy (AOR = 0.09; 95% CI: 0.04, 0.22; P  = 0.000) were significantly associated with the outcome of death. Conclusion: Treatment outcome of breast cancer is poor and requires health education and sensitization on preventive.